2019
DOI: 10.3390/atmos10090544
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Model Performance and Source Sensitivities for Sulfate Aerosol Resulting from Updates of the Aqueous- and Gas-Phase Oxidation Pathways for a Winter Pollution Episode in Tokyo, Japan

Abstract: During the Japanese intercomparison study, Japan’s Study for Reference Air Quality Modeling (J-STREAM), it was found that wintertime SO42– concentrations were underestimated over Japan with the Community Multiscale Air Quality (CMAQ) modeling system. Previously, following two development phases, model performance was improved by refining the Fe- and Mn-catalyzed oxidation pathways and by including an additional aqueous-phase pathway via NO2 oxidation. In a third phase, we examined a winter haze period in Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…, the unimolecular decomposition and reaction with (H 2 O) 2 , which may lead to an overestimation of the effect of the sCI reactions on SO 4 2− formation. 11 The contribution of the sCI reactions to the SO 4 2− formation reached a maximum of 5.0 ng m −3 (or 0.25% of the total SO 4 2− ), which is not critical to the total SO 4 2− concentration on the ground surface of the GTA region. As stated in the previous section, the calculated SO 4 2− underestimated the observed results in winter and spring seasons for Tokyo Bay and suburban regions by ∼50%.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…, the unimolecular decomposition and reaction with (H 2 O) 2 , which may lead to an overestimation of the effect of the sCI reactions on SO 4 2− formation. 11 The contribution of the sCI reactions to the SO 4 2− formation reached a maximum of 5.0 ng m −3 (or 0.25% of the total SO 4 2− ), which is not critical to the total SO 4 2− concentration on the ground surface of the GTA region. As stated in the previous section, the calculated SO 4 2− underestimated the observed results in winter and spring seasons for Tokyo Bay and suburban regions by ∼50%.…”
Section: Resultsmentioning
confidence: 89%
“…The results suggested that the maximum contribution of sCIs to SO 4 2− formation accounts for 5.0 ng m −3 , which corresponds to 0.25% of the total SO 4 2− concentration, indicating lower effects of sCIs in the targeted domain compared with previous studies. 11,12 The difference in the results derives from the incorporation of unimolecular decomposition of sCIs and the reaction with (H 2 O) 2 in this study. The SO 4 2− formation from sCIs contributes to a 0.024% decrease in radiative forcing.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In reality, different model configurations and inputs may be used to consider strategies. Itahashi et al (2019b) reported that source sensitivities can be changed by the regional chemical transport model with improved treatments for aqueous reactions.…”
Section: Discussionmentioning
confidence: 99%